PERCEPTIONS OF NURSES REGARDING PATIENT SAFETY CULTURE: A SYSTEMATIC REVIEW - Khan, Afsha; Muhammad, Dildar; Khan, Awal (Annals of Allied Health Sciences, 2019)
Objective: The objective of current literature review was to organize and identify existing knowledge regarding perception of nurses on patient safety culture. Methods: Literature was searched from year 2007 to 2017 on various databases. Total 16 full texts, peer reviewed quantitative studies conducted on nurse’s perception, attitude, knowledge and practices of safety culture were included in this review. Results: Overall, low positive attitude was found towards patient safety culture. Results of current review revealed that training on patient safety, proper staffing and management support and non-punitive response to errors might have a positive impact on improving patient safety. Conclusion: Patient safety culture was not satisfactory among nurses.